Glete de Alcântara: centenary legacy of brazilian nursing - Luciana Barizon Luchesi; Emiliane Silva Santiago; Taka Oguisso (Universidad de Alicante, 2019)
The aim was to identify relevant points in the bibliography of the Brazilian nurse Glete de Alcântara. It is a historical study of biography, which used documentary analysis. A vast documentary corpus was located, with emphasis on her memorial (1963 résumé), 54 publications, as well as articles and books mentioning her career. Through the Rockefeller Foundation, she graduated as a nurse at the University of Toronto-Canada. She initially taught at the University of São Paulo's School of Nursing, Brazil, received her BS degree in Social Sciences, at the same university and with a grant from the Kellogg Foundation, in 1951, obtained a Master of Arts degree from Teachers College, Columbia University, New York. In 1952 she was chosen to create and manage the University of São Paulo at Ribeirão Preto College of Nursing, where she remained for almost two decades as its dean. Her outstanding performance as president of the Brazilian Nursing Association, only ended with her death in 1974, while in the second term as national president of the entity, where she contributed to the scientific and legal advancement of Brazilian nursing. As a leadership model and dedication for the Nursing class Glete de Alcântara has left a great legacy of struggle for Nursing.